Ab-initio approach to the stability and the structural, electronic and magnetic properties of the (001) Znfe₂O₄ surface terminations - Salcedo Rodríguez, Karen Lizeth (2020)
We present a Density Functional Theory (DFT) based study of the structural and magnetic properties of the (001) surface of the semiconducting oxide Znfe₂O₄ (spinel structure). The calculations were performed using the DFT based ab initio plane wave and pseudopotential method as implemented in the Quantum Espresso code. The all electron Full-potential linearized-augmented-plane-wave method (FP-LAPW) was also employed to check the reproducibility of the plane wave method. In both calculations the DFT+U methodology was employed and different (001) surface terminations of Znfe₂O₄ were studied. We find that the surface terminated in Zn is the stable one. For all the (001) surface terminations our calculations predict that the Zn-Fe cationic inversion (antisites), which are defects in bulk Znfe₂O₄, becomes stable and an integral part of the surface. Also, a ferrimagnetic behavior is predicted for the case of anti-sites in the superficial layer. Our results for different properties of the surface of Znfe₂O₄ are compared with those obtained in bulk samples and those reported in the literature.